Religion, culture, and development: The pneuma-diaconal perspective of African Pentecostalism - White, Peter (Stellenbosch Theological Journal, 2021)
We cannot realistically discuss development without factoring religion into the analysis. In the same way, we cannot design any economic development plan without acknowledging the influence of religion on its implementation. The fact is that, many economic development policies require a change from old values, attitudes, beliefs and behaviour patterns of the citizenry to those that are supportive of the new policy. Religious practices and beliefs have important consequences for the economic development of a community or nation. The relationship between religion and development is likely to be complementary as long as religious beliefs and practices promote "moderation" rather than "˜extremes". This article therefore discusses how Pentecostalism has been used as a reference point in addressing religio-cultural and socio-economic needs of Africans. The study uses Spiritual capital theory and pneuma-diaconal mission theory to unearth the impact of African Pentecostalism in the socio-economic lives of Ghanaians and more especially Africans.